Left Atrial Appendage Closure for Primary and Secondary Stroke Prevention in Patients With Hypertrophic Cardiomyopathy and Atrial Fibrillation: A Pilot Study - Mo, Bin-Feng; Zhang, Rui; Yuan, Jia-Li; Sun, Jian; Zhang, Peng-Pai; Li, Wei; Chen, Mu; Cai, Xing-Xing; Yu, Yi-Chi; Wang, Qun-Shan; Li, Yi-Gang (Frontiers in Cardiovascular Medicine, 2021)
Background: The aim of this study was to investigate the efficacy of left atrial appendage closure (LAAC) for primary and secondary stroke prevention in patients with hypertrophic cardiomyopathy (HCM) and atrial fibrillation (AF). Methods: This pilot study enrolled 36 patients with HCM and AF who underwent LAAC between April 2017 and December 2019, of whom 22 were for primary stroke prevention and 14 were for secondary prevention. Results: The patients enrolled in this study were nonobstructive (86.1%) or mild obstructive (13.9%) HCM. Patients in the Secondary Prevention Group had a higher CHA2DS2-VAS score (5.1 ± 1.4 vs. 2.6 ± 1.6, P < 0.001) and a higher HAS-BLED score (2.8 ± 1.0 vs. 1.5 ± 0.9, P < 0.001) compared with those in the Primary Prevention Group. Successful closure with satisfactory seals (residual leak ≤ 5 mm) was achieved in all the patients with complete occlusion in 86.4% of the Primary Prevention Group and 92.9% of the Secondary Prevention Group. Procedure-related complications included one pericardial effusion and one groin hematomas. One device related thrombus was identified in the Secondary Prevention Group and resolved after anticoagulation. During a mean of 28.4 months follow-up, one bleeding event was recorded. There were no thromboembolic events or deaths in either group with 97.2% of the patients obtaining freedom from OAC therapy. Conclusions: Initial results suggest that LAAC can be a safe and feasible alternative for primary and secondary stroke prevention in selected patients with HCM and AF. Further studies with a larger sample are required.